Effects of standardization and customization level on service quality, customer satisfaction and loyalty, and moderating roles of service nature and customer needs - Kasiri, Leila Agha (2015)
The issue of whether or not total standardization or total customization is really a workable solution in Service Quality has been widely debated. The Standardization and Customization of service decisions has been viewed as a field with completely two extremes. Looking at Gronroos theory of Service Quality which proposes that service quality has two dimensions or aspects namely technical and functional quality, this study is an attempt to further develop the Gronroos theory on service quality to venture into service marketing contributing to Customer Relationship Management (CRM) and eliminating the paradox that standardization and customization cannot go hand in hand. This is done by integrating customization-standardization continuum in Gronroos model using hotel, hospital and education industries, and samples has been drawn from various classes of hotels, hospitals and from 'higher learning institution in Malaysia using the Structural Model Analysis where Partial Least Square SEM (PLS-SEM) is employed. Expert opinions were sought in the design and wordings of questionnaires pertaining to Hotel, Hospital and University before they were distributed. A pilot test was then conducted before the actual study took place. The analysis of data went through path analysis, stringent mediating and moderating tests to test the hypothesis. The results indicate the simultaneous presence of standardization and customization, although the level may vary. The results suggest that between standardization and customization, standardization has a stronger impact on technical and functional quality dimensions of service quality. The results also show that the impact of customization on service quality dimensions are similar whereas the impact of standardization are different. These imply that efficiency and effective management of services lead to perception of better service quality in the three service industries studied in Malaysia. Confirming previous studies customer satisfaction mediates the relationship between different aspects of service quality (technical and functional quality) and customer loyalty. On separating the industries based on the heterogeneity of the data, the study showed that moderating effects of service nature and customer needs on the relationship between standardizationfcustomization and technical/functional quality differ across industries.